Urban Sprawl as a Risk Factor in Motor Vehicle Occupant and Pedestrian Fatalities: Update and Refinement. Issue 1 (January 2015) - Ewing, Reid; Hamidi, Shima
The United States once had the safest transportation system in the developed world, but the U.S. traffic safety record has fallen behind that of other developed countries. Only with an understanding of the basic causes of traffic crashes can policies be devised to reduce crash numbers. Metropolitan sprawl has been implicated as one cause of traffic crashes because sprawl generates long automobile trips with associated high crash exposure. A decade ago, compactness–sprawl indexes were developed for metropolitan areas and counties. These indexes have been widely used in health and other research, including a 2003 study of traffic fatalities. In the current study, the original county index was first updated to 2010; then, a refined index that accounts for more relevant factors was developed. Finally, the 2003 results were replicated and expanded. Principal component analysis was used to extract county compactness–sprawl indexes from variables related to development density, mix of land use, population and employment centering, and street accessibility. These indexes were validated against county commuting data and related to county traffic fatality rates through multilevel modeling. When covariates were controlled for, sprawl was found to be associated with significantly higher traffic fatality rates and significantly higher pedestrian fatality rates when adjusted for exposure. The most likely explanations are the greater number of vehicle miles driven and the higher traffic speeds in sprawling environments. Recognition of this relationship is important because it adds traffic safety to other health risks associated with urban sprawl in the literature.